Economic and humanistic burden of HPV-related disease in Indonesia: A qualitative analysis - Marisa Felsher; Didik Setiawan; Stefan Varga; Richard Perry; Danielle Riley; Rebecca Newman; Abigail Beveridge; Charlotte Oswald; Smita Kothari; Isaya Sukarom; Maarten Postma (Taylor & Francis Group, 2023)
The burden of human papillomavirus (HPV) and HPV-related cancers and genital warts is increasing in developing countries, including Indonesia. The objective of this study was to qualitatively explore the humanistic and economic burden of these HPV-related diseases in patients in Indonesia. In 2021, in-depth interviews and focus groups were conducted with patients (N = 18) with HPV-related diseases and healthcare professionals (HCPs; N = 10) specialised in treating these patients. Interviews explored the physical, mental, social, and economic burden of HPV-related diseases. Patients emphasised the psychological and social burden of HPV-related diseases, which negatively impacted their mental state and close relationships. Treatment for HPV-related diseases was also associated with a substantial cost, which health insurance only partially alleviated. HCPs understood the physical negative impact of HPV-related diseases, but some understated patients' social, psychological, and financial burden. This research underscores the substantial economic and humanistic burden of HPV-related diseases that could be prevented by vaccination. In addition, it highlights the need for novel interventions to reduce negative psychosocial consequences of HPV-related diseases in Indonesia. Increased HCP education of the broader humanistic impacts of HPV-related diseases may improve patient support and increase awareness for preventive strategy.